If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 9 + -1(-12a + 24) = 15 Reorder the terms: 6a + 9 + -1(24 + -12a) = 15 6a + 9 + (24 * -1 + -12a * -1) = 15 6a + 9 + (-24 + 12a) = 15 Reorder the terms: 9 + -24 + 6a + 12a = 15 Combine like terms: 9 + -24 = -15 -15 + 6a + 12a = 15 Combine like terms: 6a + 12a = 18a -15 + 18a = 15 Solving -15 + 18a = 15 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 18a = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 18a = 15 + 15 18a = 15 + 15 Combine like terms: 15 + 15 = 30 18a = 30 Divide each side by '18'. a = 1.666666667 Simplifying a = 1.666666667
| x+4-9+4x-9=180 | | .069x+x=59 | | -3(x-4)=12-3x | | 42-12t=30 | | 2x-5x=5-9 | | (2x/3)-(4x/5) | | (x+4)2=(4-x)(4+x) | | 2x/3-4x/5 | | 8(x+1)=8x+1 | | 11-3k=-4(1+2k) | | xa=d | | 56=-1+3x | | 7(2a-8)+6=-92 | | 5-9a-14/3(2a) | | Z=-5z | | 2x^3-4x^2= | | 2l+6=6-10 | | Y-2+3x=6+5x | | 1/2x-y=3 | | 4x-(2x-10)=2x-6 | | sqrtx+2=3 | | 12x+10=14x | | -5(3-q)+4=5q | | 5(b+1)-6=2b-16 | | 8.364km= | | 1/3=4/6q | | 2y+3(0)y=10-0 | | 6m-2=-2-7m-m | | 15(x-3)=105 | | 3/4-3/4=0 | | -8(-2b+2)=-128 | | -8(1-4p)=120 |